Genome-Wide Identification of the Oxidative Stress 3 (OXS3) Gene Family and Analysis of Its Expression Pattern During Ovule Development and Under Abiotic Stress in Cotton - Yu Chen; Rui Yang; Haojie Wang; Xianghui Xiao; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Renhai Peng; Guodong Chen; Yongbo Wang; Pengtao Li (Biology)
Oxidative Stress 3 (OXS3) encodes a plant-specific protein that makes great contributions to a plant’s stress tolerance. However, reports on genome-wide identification and expression pattern analyses of OXS3 were only found for Arabidopsis, wheat, and rice. The genus Gossypium (cotton) serves as an ideal model for studying allopolyploidy. Therefore, two diploid species (G. raimondii and G. arboreum) and two tetraploid species (G. hirsutum and G. barbadense) were chosen in this study for a bioinformatics analysis, resulting in 12, 12, 22, and 23 OXS3 members, respectively. A phylogenetic tree was constructed using 69 cotton OXS3 genes alongside 8 Arabidopsis, 10 rice, and 9 wheat genes, which were classified into three groups (Group 1–3). A consistent evolutionary relationship with the phylogenetic tree was observed in our structural analysis of the cotton OXS3 genes and the clustering of six conserved motifs. Gene duplication analysis across the four representative Gossypium species suggested that whole-genome duplication, segmental duplication, and tandem duplication might play significant roles in the expansion of the OXS3 gene family. Some existing elements responsive to salicylic acid (SA), jasmonic acid (JA), and abscisic acid (ABA) were identified by cis-regulatory element analysis in the promoter regions, which could influence the expression levels of cotton OXS3 genes. Furthermore, the expression patterns of the GhOXS3 gene were examined in different tissues or organs, as well as in developing ovules and fibers, with the highest expression observed in ovules. GhOXS3 genes exhibited a more pronounced regulatory response to abiotic stresses, of which ten GhOXS3 genes showed similar expression patterns under cold, heat, salt, and drought treatments. These observations were verified by quantitative real-time PCR experiments. These findings enhance our understanding of the evolutionary relationships and expression patterns of the OXS3 gene family and provide valuable insights for the identification of vital candidate genes for trait improvement in cotton breeding.